Extração das proteínas do fubá de milho e obtençãode hidrolisados protéicos com baixo teror de fenilalanina - Michely Capobiango (2006)
Extraction of proteins from Brazilian corn flour and obtention of proteinhydrolysates with low phenylalanine content. Considering the important position of corn in the diet of the Brazilian people, this cereal was used as raw matter to prepare dietary supplements for phenylketonuria based on protein hydrolysates. Initially, different chemical methods and an enzymatic one were tested for protein extraction from Braziliancorn flour. For the chemical extraction, the sequential alkaline-alcoholic method was the most efficient, reaching a yield of 88 %. For the enzymatic extraction, a protease of Bacillus liccheniformis was used. The time and the temperature employed in this method influenced the extraction yield. The best results were obtained for 5, 15 and 24 h at 55 °C, reaching a yield of 84 %. Then, ten enzymatic hydrolysates were prepared by the action of corolase PP. Aiming the reduction of phenylalanine content, different conditions were tested, such as protein extract concentration; enzyme:substrate ratio; protein:activated carbon ratio; mode of use of activated carbon and the use of lyophilization. After passingthe hydrolysates through a column containing activated carbon for removing phenylalanine, second derivative spectrophotometry was used to determine the amount of this amino acid. The corolase PP and the activated carbon showed to be efficient to obtain protein hydrolysates with Phe content within the limit established Brazilian legislation.